2021
DOI: 10.1364/ol.435197
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional tunable gradient metasurfaces for terahertz beam splitting and light absorption

Abstract: Obtaining functional devices with tunable features is beneficial to advance terahertz (THz) science and technology. Here, we propose multifunctional gradient metasurfaces that are composed of a periodic array of binary Si microcylinders integrated with V O 2 and graphene. The metasurfaces act as transmittive (reflective) beamsplitters for the dielectric (metallic) phase of V O 2 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, in the concept of digital metasurfaces, it has been shown that by employing binary or 1-bit ('0' and '1') elements with only π phase shift it is possible to achieve beam steering (see e.g. [63]). In case of active control over the binary elements, programmable metasurfaces are realized [23].…”
Section: Optical Design Of the Reprogrammable Metasurface Beam Steerermentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the concept of digital metasurfaces, it has been shown that by employing binary or 1-bit ('0' and '1') elements with only π phase shift it is possible to achieve beam steering (see e.g. [63]). In case of active control over the binary elements, programmable metasurfaces are realized [23].…”
Section: Optical Design Of the Reprogrammable Metasurface Beam Steerermentioning
confidence: 99%
“…The most common examples of these active materials are liquid crystals [30,31], transparent conducting oxides, such as indium tin oxide (ITO) [32][33][34][35][36][37][38][39], III-V multiplequantum-wells [40], or phase change materials (PCMs), such as chalcogenide glasses (GST, GSST) [41][42][43][44][45][46] and vanadium dioxide (VO 2 ) [47][48][49][50][51][52][53][54][55][56][57]. To achieve active metasurfaces for the mid-infrared and far-infrared ranges, graphene [58], GST [59] and VO 2 [42,[60][61][62][63][64] are potential candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, we figure out that Erçaglar et al proposed multifunctional tunable gradient MSs which were composed of a periodic array of binary Si microcylinders integrated with VO 2 and graphene for THz beam splitting and light absorption. [78] So, we try using an optically thick film of VO 2 as a bottom reflector (for the metallic phase) to obtain a multifunctional device, whose results are displayed in Figure 6b. It can be seen that most of the energy is reflected in this MS structure whose bottom metal plate is replaced with the VO 2 (for the metallic phase).…”
Section: The Realization Of the Eit Behaviormentioning
confidence: 99%
“…Dielectric metasurfaces (DMs) have been recently employed for flat optics wavefront manipulation due to their low resonance-induced heating as compared to their plasmonic counterparts and CMOS-compatible fabrication processes [ 2 , 3 , 4 ]. Remarkably, asymmetric DMs composed of meta-atoms with broken in-plane inversion symmetry can support high-Q resonances originating from the symmetry-protected quasi-bound states in the continuum (q-BIC) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%